Responsive Neurostimulation Targeting the Anterior, Centromedian and Pulvinar Thalamic Nuclei and the Detection of Electrographic Seizures in Pediatric and Young Adult Patients - Beaudreault, Cameron P.; Muh, Carrie R.; Naftchi, Alexandria; Spirollari, Eris; Das, Ankita; Vazquez, Sima; Sukul, Vishad V.; Overby, Philip J.; Tobias, Michael E.; McGoldrick, Patricia E.; Wolf, Steven M. (Frontiers in Human Neuroscience, 2022)
Background: Responsive neurostimulation (RNS System) has been utilized as a treatment for intractable epilepsy. The RNS System delivers stimulation in response to detected abnormal activity, via leads covering the seizure foci, in response to detections of predefined epileptiform activity with the goal of decreasing seizure frequency and severity. While thalamic leads are often implanted in combination with cortical strip leads, implantation and stimulation with bilateral thalamic leads alone is less common, and the ability to detect electrographic seizures using RNS System thalamic leads is uncertain. Objective: The present study retrospectively evaluated twelve patients with RNS System depth leads implanted in the thalamus, with or without concomitant implantation of cortical strip leads, to determine the ability to detect electrographic seizures in the thalamus. Detailed patient presentations and lead trajectories were reviewed alongside electroencephalographic (ECoG) analyses. Results: Anterior nucleus thalamic (ANT) leads, whether bilateral or unilateral and combined with a cortical strip lead, successfully detected and terminated epileptiform activity, as demonstrated by Cases 2 and 3. Similarly, bilateral centromedian thalamic (CMT) leads also demonstrated the ability to detect and halt electrographic seizures, even without the aid of cortical leads, as seen in Cases 6 and 9. Detections of electrographic seizures in thalamic nuclei did not appear to be affected by whether the patient was pediatric or adult at the time of RNS System implantation. Sole thalamic leads paralleled the combination of thalamic and cortical strip leads in terms of preventing the propagation of electrographic seizures. Conclusion: Thalamic nuclei present a promising target for detection and stimulation via the RNS System for seizures with multifocal or generalized onsets. and provide a modifiable, reversible therapeutic option for patients who are not candidates for surgical resection or ablation.